Pemanfaatan Video Edukasi dan Pelatihan Canva untuk Mendukung Kesehatan Anak Panti Asuhan - Avid Wijaya; Prima Soultoni Akbar; Eiska Rohmania Zein (Pusat Riset dan Inovasi Nasional, 2025)
The Al-Ikhlas Orphanage, located in Sidorahayu Village, Malang, faces challenges related to low levels of health education and limited awareness of non-communicable diseases (NCDs) among the children. These issues stem from restricted resources and inadequate access to relevant health information.This community service program aims to enhance the children’s health knowledge, digital literacy, and awareness of NCDs. The implementation methods include developing educational video content tailored to the children’s level of understanding, conducting training on video creation using the Canva application and promoting healthy lifestyle practices, as well as evaluating the program through satisfaction surveys, interviews, and skill assessments.The targeted outcomes include improved knowledge among orphanage children about NCD prevention, acquisition of basic skills in educational video production, documentation of the activities in video format, and publication of a scientific article in a national journal.The results demonstrate an increase in the children’s understanding of the importance of NCD prevention, enhanced practical skills in producing educational videos using Canva (including template selection, addition of text, images, and audio, as well as video export), and greater motivation and enthusiasm among participants to independently create health-related educational content.